Competências linguísticas na prova do ENEM : uma abordagem sociolinguística - Andrade, Sammela Rejane de Jesus (2015)
Based on the theoretical reference of Sociolinguistics, and constant approaches in the National Curriculum Parameters - NCP and the National Program of Didactic Books –NPDB, it is proposed to analysis of the definition and implementation of the assessment of language skills present in the language of test, codes and its technologies, in order to observe how the theories of language and language descriptions in the event in question are treated, based on the Labov studies (2008), Soares (1986), Faraco (2008), Bagno (2012), among others . Considering the language from the sociolinguistic conception as heterogeneous, multiple and in permanent construction we raised the questioning of how to treat this heterogeneity and mutation, in a closed and limited space in the case a selection examination (objective test of ENEM), which stipulates skills to be achieved and the means for this to occur. The analysis takes as corpus official documentation available to the candidates who provide the exam ie the Participant's guide, the Edital with standards for the process, and the tests from the years 2000 to 2012, with the aim of correlate the information contained in this material to public policies directed to basic education, more effectively to high school, and mainly discussing the treatment of linguistic variation through the propositions of continuous Bortoni-Ricardo (2004a). The analysis showed that there is a congruence as the requirements of official documents and the guiding rulers of the test, however, the observation of the questions showed how we still need to change for it to happen more effective variational approach in the ENEM and in the Portuguese language teaching.